Self-Employed Individuals With and Without Employees: Individual, Social and Economic Level Differences - Petrescu, Maria (Senate Hall, 2016)
This paper focuses on the differences between solo self-employed individuals and self-employed persons that hire employees, in terms of individual, social and economic variables. The study is based on Dyer's (1994) model of entrepreneurial careers and Schwartz' (1992, 1994) values inventory and uses data from Wave 7 of the European Social Survey released in 2016. The analysis found that, compared to solo self-employed, self-employed individuals with employees have higher scores regarding their need for power values, i.e., they attach higher importance to achieving high social status and prestige, authority, wealth, and a positive public image. Moreover, the level of overall happiness is higher for self-employed with employees, even when controlling for their higher incomes. On the other hand, entrepreneurs attaching a high importance to self-direction (including job autonomy) were more often found to be working on their own (i.e., solo self-employed) Keywords: self-employed, entrepreneurs, need for achievement, need for power, need for self-direction
Keywords: self-employed|entrepreneurs|need for achievement|need for power|need for selfdirection